Prevention Program Performance Improvement Strategy and Control of Non-Communicable Diseases at Blega Health Center, Bangkalan District - Agus Salim Burhanuddin; Katmini; Yuly Peristiowati (Journal for Quality in Public Health, 2023)
The increase in cases of Non-Communicable Diseases (NCDs) will significantly increase the burden on society and the government because handling them requires a short time, large costs, and high technology. NCD cases are not transmitted but are deadly and result in individuals becoming less or less productive but NCDs can be prevented by controlling risk factors through early detection. Overall, this residency was carried out to provide an overall picture of the Strategy for Improving the Performance of the Non-Communicable Disease Prevention and Control Program at the Blega Health Center, Bangkalan Regency.  In this article, the method used is the residency method, which is the process of exploring the place, condition, and situation of the residency and determining problems using the Fishbone method Implementation and strategies in improving services The Non-communicable disease program has been carried out well, but there are still some weaknesses, namely restrictions on activities in the Covid-19 pandemic, the program coordinator is still new,  Program regulation is still partial, budget constraints and lack of community participation.